INFORMATION ON FINANCIAL INSTRUMENTS INCLUDED IN ANNUAL FINANCIAL STATEMENTS - Marius Gust; Laura Pănoiu (Strategii Manageriale, 2013)
This survey aims at emphasizing several aspects of the recognition, measurement and presentation of information on capital assets and how they are reflected in accounting. In this respect, here is a presentation of the calculation, preparation and regulation of impairment that can affect capital assets and the way accounting entries may influence the financial status and performance of a company. Although the bookkeeping variants of asset impairment, namely the Romanian and the international ones, are different, the information reported in annual financial statements is the same and assets are shown at their fair values. The issues approached in the paper herein are vast and they open new prospects to scientific research.